2008
DOI: 10.1002/cncr.23334
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cyclic guanosine monophosphate‐dependent protein kinase in metastatic colon carcinoma cells blocks tumor angiogenesis

Abstract: Microbial production of desired compounds provides an efficient framework for the development of renewable energy resources. To be competitive to traditional chemistry, one requirement is to utilize the full capacity of the microorganism to produce target compounds with high yields and turnover rates. We use integrated computational methods to generate and quantify the performance of novel biosynthetic routes that contain highly optimized catalysts. Engineering a novel reaction pathway entails addressing feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Surprisingly, the size of the polyps from animals treated with sildenafil did not differ from those from control animals. This result was not anticipated based upon work with human colon cancer cell lines that predicts anti-tumor effects of cGMP signaling that include inhibition of proliferation, increased apoptosis, and inhibition of angiogenesis (9,40,41). Other in vitro studies have demonstrated that cGMP signaling suppresses proliferation without affecting apoptosis, and notably, that it can induce goblet cell differentiation (17,42).…”
Section: Discussionmentioning
confidence: 96%
“…Surprisingly, the size of the polyps from animals treated with sildenafil did not differ from those from control animals. This result was not anticipated based upon work with human colon cancer cell lines that predicts anti-tumor effects of cGMP signaling that include inhibition of proliferation, increased apoptosis, and inhibition of angiogenesis (9,40,41). Other in vitro studies have demonstrated that cGMP signaling suppresses proliferation without affecting apoptosis, and notably, that it can induce goblet cell differentiation (17,42).…”
Section: Discussionmentioning
confidence: 96%
“…Expression of PKG-I is downregulated in multiple tumor tissues compared with respective normal tissues (26). Activation of cGMP/PKG pathway inhibits breast or colon cancer cell growth and angiogenesis, and it induces these cells' apoptosis (13,27,47). A death-associated protein kinase 2 has been identified to be the substrate of PKG-I and mediates PKG-Iinduced breast cancer cell apoptosis (25).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies suggested that PKG may be proapoptotic or anti-apoptotic, depending on cell types (19, 50). Recently, a proapoptotic role of PKG has been shown in various cancer cell types, linking cGMP/PKG signaling to anti-tumor activities (13,15,16,27,47). Expression of PKG-I is downregulated in multiple tumor tissues compared with respective normal tissues (26).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The expression of PKG1 is reduced in colon tumors relative to matched normal tissue and is barely detectable in colon cancer cell lines (13). Ectopic reexpression of PKG1 in colon cancer cells blocks xenograft growth (13,17), presumably by inhibiting ␤-catenin/TCF (19) and hypoxia signaling (18). PKG2 expression is not reduced in colon tumors (not shown) but was not detected in any of the colon cancer cell lines examined in the present study.…”
Section: Discussionmentioning
confidence: 99%